Predictors of rapidly progressive interstitial lung disease and prognosis in Chinese patients with anti-melanoma differentiation-associated gene 5-positive dermatomyositis - Li, Meiqi; Zhao, Xuli; Liu, Baocheng; Zhao, Yaqi; Li, Xinya; Ma, Zhenzhen; Yang, Qingrui (Frontiers in Immunology, 2023)
Background: Rapidly progressive interstitial lung disease (RP-ILD) is the most serious complication of anti-melanoma differentiation-associated gene 5-positive dermatomyositis (anti-MDA5 + DM). This study was performed to assess the prognostic factors of patients with anti-MDA5 + DM and the clinical characteristics and predictors of anti-MDA5 + DM in combination with RP-ILD.In total, 73 MDA5 + DM patients were enrolled in this study from March 2017 to December 2021. They were divided into survival and non-survival subgroups and non-RP-ILD and RP-ILD subgroups.The lactate dehydrogenase (LDH) concentration and prognostic nutritional index (PNI) were independent prognostic factors in patients with anti-MDA5 + DM: the elevated LDH was associated with increased mortality (p = 0.01), whereas the elevated PNI was associated with reduced mortality (p < 0.001). The elevated LDH was independent risk prognostic factor for patients with anti-MDA5 + DM (HR 2.42, 95% CI: 1.02-4.83, p = 0.039), and the elevated PNI was independent risk prognostic factor (HR, 0.27; 95% CI, 0.08 -0.94; p = 0.039). Patients who had anti-MDA5 + DM with RP-ILD had a significantly higher white blood cell count and LDH concentration than those without RP-ILD (p = 0.007 and p = 0.019, respectively). In contrast, PNI was significantly lower in patients with RP-ILD than those without RP-ILD (p < 0.001). The white blood cell count and elevated LDH were independent and significant risk factors for RP-ILD (OR 1.54, 95% CI: 1.12 -2.13, p = 0.009 and OR 8.68, 95% CI: 1.28 -58.83, p = 0.027, respectively), whereas the lymphocyte was an independent protective factor (OR, 0.11; 95% CI, 0.01 -0.81; p = 0.03).The elevated LDH and elevated PNI were independent prognostic factors for patients with anti-MDA5 + DM. The elevated LDH was independent risk factor for RP-ILD. Patients with anti-MDA5 + DM could benefit from the measurement of LDH and PNI, which are inexpensive and simple parameters that could be used for diagnosis as well as prediction of the extent of lung involvement and prognosis.